Analysis of Cohesivenes in Descriptive text Written by Undergraduate Students - Pahrul Hadi, Muhammad Zaki (English Education: Jurnal Tadris Bahasa Inggris, 2021)
Cohesiveness or the use of cohesive devices is a critical aspect of writing skill. It is one of the primary characteristics that should be mastered when writing well. The purpose of this article was to examine the use of cohesive devices in descriptive text written by undergraduate students in the Banking Department of STIE KERJASAMA Yogyakarta's third semester. This study examined the use of cohesive devices in each of the students' descriptive texts. The study's data set consisted of ten texts. The study identified four significant findings by employing a mixed research design and drawing on Halliday and Hasan's (1976) influential theory of cohesion. To begin, students' English texts contain a variety of cohesive devices (reference, conjunction, substitution, ellipses, and lexical cohesion). Whereas there are three types of cohesive devices that are frequently used in texts: reference, lexical cohesion, and conjunction. The study's findings have repercussions for pedagogy, theory, academic writing, and future research.